The apostolic age in patristic thought - Hilhorst, A. (Vigiliae Christianae, Supplements, 2004)
This volume deals with how Christians of the first centuries looked back on the period of the nascent Church. Thanks to the incomparable stature of its founder, Jesus Christ, who had descended from heaven and commissioned his Apostles, this period was authorative for all Christians in matters of doctrine, institutions, rites and morality, a new phenomenon in the Graeco-Roman world. Its implications are explored in sixteen essays dealing with various subjects such as liturgy, the canon of Scriptures, the role of miracles, art, monasticism, and ministry. All contributions, taking into account both the views of individual Church fathers and Gnostic and Manichaean texts, make a large amount of primary material available.